Designing of Flexible Multi-Microcontroller Based Training System - Selvakumar, Raja Saravana Kumar; Kamarul Hawari, Ghazali; Nik Mohd Kamil, Nik Yusof (2010)

(untitled)
In traditional Embedded Control Technology courses, students learn to develop assembly language programs to control peripherals, handle interrupts, and perform I/O operations. However, students find the subject are diffcult as the subject is presented in a lecture format. Unfortunetly, this Embedded Controller Technology (ECT) course is a compulsory course in any electrical or electronic field of engineering. This paper aims to describe development of a flexible multi-microcontroller training system based on 8-bit microcontroller in Microchip, Freescale (formerly Motorola) and Intel family. For this reason, a new laboratory evaluation tool (UMP-EVT) specifically will be designed to be as a learning tool for those who intend to learn microcontroller and for use in the academic environment. With an extensive of this training system, it could let the user to get start with their microcontroller application efficiently. In addition, it is further boosted by the introduction of Integrated Development Environment (IDE) features in order to create user-friendly environment. By using this UMP-EVT, users are exposed to practical experience of the microcontroller and provide an easy path to learn this intelligent electronic device in short time. In this respect, this UMP-EVT would be applicable for education and expose the electrical engineering students to the understanding fundamental of microcontroller in electronic design field. Keywords: Educational, MCS51 microcontroller, HC11 microcontroller, PIC microcontroller